2009
DOI: 10.1007/s00005-009-0040-y
|View full text |Cite
|
Sign up to set email alerts
|

Fc receptor-targeted mucosal vaccination as a novel strategy for the generation of enhanced immunity against mucosal and non-mucosal pathogens

Abstract: Numerous studies have demonstrated that targeting immunogens to Fcgamma receptors (FcgammaR) on antigen (Ag)-presenting cells (APC) can enhance humoral and cellular immunity in vitro and in vivo. FcgammaR are classified based on their molecular weight, IgG-Fc binding affinities, IgG subclass binding specificity, and cellular distribution and they consist of activating and inhibitory receptors. However, despite the potential advantages of targeting Ag to FcR at mucosal sites, very little is known regarding the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
26
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 122 publications
2
26
0
Order By: Relevance
“…Blockade of the Fc-␥ receptor led to a clear reduction in uptake of L. monocytogenes, lending support to the hypothesis that anti-Frl MAb-mediated opsonization is the most likely mechanism of antilisterial immune resistance. Indeed, some recent studies have focused on using the Fc-␥ receptors as vaccine targets to induce both cellular and humoral immune responses against extracellular and intracellular pathogens (1,22). Importantly, it has been shown that the targeting of the Fc-␥ receptor with Francisella tularensis, an intracellular bacterium, combined with an anti-Francisella tularensis lipopolysaccharide MAb, led to enhancement of protective immunity against subsequent challenge with this pathogen (34).…”
Section: Discussionmentioning
confidence: 99%
“…Blockade of the Fc-␥ receptor led to a clear reduction in uptake of L. monocytogenes, lending support to the hypothesis that anti-Frl MAb-mediated opsonization is the most likely mechanism of antilisterial immune resistance. Indeed, some recent studies have focused on using the Fc-␥ receptors as vaccine targets to induce both cellular and humoral immune responses against extracellular and intracellular pathogens (1,22). Importantly, it has been shown that the targeting of the Fc-␥ receptor with Francisella tularensis, an intracellular bacterium, combined with an anti-Francisella tularensis lipopolysaccharide MAb, led to enhancement of protective immunity against subsequent challenge with this pathogen (34).…”
Section: Discussionmentioning
confidence: 99%
“…Both human and mouse Fc␥RI are high-affinity Fc␥R, which means that they can bind the Fc region of IgG when in monomeric form (25). Unlike the more ubiquitously expressed Fc␥RII and Fc␥RIII, Fc␥RI receptors are constitutively expressed primarily on professional antigen-presenting cells (APCs) (dendritic cells [DC] and macrophages [M]) (25,52), and their expression can be induced on polymorphonuclear leukocytes (PMN) (42,60). Fc␥RI receptors are activating receptors, providing solely stimulatory signals to the antigen-presenting cell (25).…”
mentioning
confidence: 99%
“…These results further suggest that Hc may transport R4 as "cargo" across the mucosal interface, as has been observed for other protein domains fused to Hc (27). Future studies will be needed to determine whether R4 can augment responses to nasal vaccination by targeting Hc to Fc␥Rs expressed on DCs and APCs located in the nasal mucosa (14). During the early phase of the primary immune response, antibodies directed against appropriate neutralizing epitopes may lack sufficient avidity to neutralize BoNT.…”
Section: Discussionmentioning
confidence: 54%